Targeting high value metals in lithium-ion battery recycling via shredding and size-based separation. (May 2016) - Wang, Xue; Gaustad, Gabrielle; Babbitt, Callie W.
Highlights: Proposed mechanical process can effectively enrich LIB materials into size fractions. Resulting fractions could help recyclers choose more optimal recycling technologies. Results show that pre-sorting LIBs by cathode chemistry could improve recovery. Labeling may also greatly improve the recycling and recovery process for LIBs. Abstract: Development of lithium-ion battery recycling systems is a current focus of much research; however, significant research remains to optimize the process. One key area not studied is the utilization of mechanical pre-recycling steps to improve overall yield. This work proposes a pre-recycling process, including mechanical shredding and size-based sorting steps, with the goal of potential future scale-up to the industrial level. This pre-recycling process aims to achieve material segregation with a focus on the metallic portion and provide clear targets for subsequent recycling processes. The results show that contained metallic materials can be segregated into different size fractions at different levels. For example, for lithium cobalt oxide batteries, cobalt content has been improved from 35% by weight in the metallic portion before this pre-recycling process to 82% in the ultrafine (<0.5 mm) fraction and to 68% in the fine (0.5–1 mm) fraction, and been excluded in the larger pieces (>6 mm). However, size fractions across multiple battery chemistries showed significant variability in material concentration. This finding indicates that sorting by cathode before pre-treatment could reduce the uncertainty of input materials and therefore improve the purity of output streams. Thus, battery labeling systems may be an important step towards implementation of any pre-recycling process.